Electrochemical behavior of plant growth stimulator 1-naphthaleneacetic acid and its voltammetric determination using boron doped diamond electrode - Janíková, Lenka; Chýlková, Jaromíra; Šelešovská, Renáta; Sedlák, Miloš; Váňa, Jiří; Dušek, Libor; Bartáček, Jan (My University, 2020)
Electrochemical behavior of a plant growth stimulator 1-naphthaleneacetic acid (NAA) was firstly studied using a boron doped diamond electrode. It was found that NM provided two irreversible anodic signals about the potential values of + 1450 and + 1630 mV, respectively, in an acidic medium. Products of the observed elecrode reaction were identified using gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (H-1 NMR) techniques. Based on the obtained results, the oxidation mechanism of studied compound was firstly proposed. Subsequently, voltammetric method for NAA determination was developed with the following statistical parameters: LOD = 0.09 mu g mL(-1) and RSD11 = 2.1% (10.8 mu g mL(-1)). Moreover, this work brings approach for analysis of stimulators mixtures for the first time as well. The proposed method allows the determination of NM, IBA, and IAA in mixed formulations without application of any sophisticated separation techniques. This new method was finally applied for NM determination in commercially available herbicide preparation.
Elektrochemické chování rostlinného stimulátoru růstu 1-naftalenoctové kyseliny a její voltametrické stanovení s využitím borem dopované diamantové elektrody.
Keywords: plant growth stimulator; 1-Naphtaleneacetic acid; voltammetry; boron doped diamond electrode; rostlinný stimulátor růstu; kyselina 1-naftalenoctová; voltametrie; borem dopovaná diamantová elektroda